The Effect of the Implementation of Student Teams–Achievement Divisions (STAD) Cooperative Learning on Students’ English Learning Outcomes at SMK Negeri 1 Manado - Iknasia Reiti Sompotan; Mister Gidion Maru; Ceisy Nita Wuntu (CV Wahana Publikasi, 2026)
The increasing demand for English proficiency in vocational education requires the implementation of innovative teaching strategies that actively engage students in the learning process. This study investigates the effect of the Student Teams–Achievement Divisions (STAD) cooperative learning model on students’ English learning outcomes at SMK Negeri 1 Manado. The study employed a qualitative descriptive approach involving twenty eleventh-grade students and one English teacher as research participants. Data were collected through classroom observations, in-depth interviews, documentation, reflective journals, and learning records. The implementation of STAD was conducted through heterogeneous group formation, class presentations, team study activities, individual quizzes, and team recognition sessions. The findings revealed that the STAD model significantly improved students’ participation, motivation, confidence, and engagement in English learning. Students demonstrated greater willingness to communicate in English, increased collaboration skills, and improved understanding of vocabulary, grammar, reading comprehension, and speaking activities. The study further identified four major themes explaining the effectiveness of STAD: reduction of language anxiety, enhancement of intrinsic motivation, effectiveness of peer scaffolding, and development of social competencies. Despite challenges related to time management and unequal participation during the early stages of implementation, the model proved successful in creating a more interactive and student-centered learning environment. The findings suggest that STAD is an effective pedagogical approach for improving English learning outcomes in vocational schools while simultaneously fostering collaborative and communicative competencies required in contemporary workplaces.